Environmental enrichment does not influence hypersynchronous network activity in the Tg2576 mouse model of Alzheimer’s disease - Bezzina, Charlotte (Front Aging Neurosci, 2015)
The cognitive reserve hypothesis claims that the brain can overcome pathology by reinforcing preexistent processes or by developing alternative cognitive strategies. Epidemiological studies have revealed that this reserve can be built throughout life experiences as education or leisure activities. We previously showed that an early transient environmental enrichment (EE) durably improves memory performances in the Tg2576 mouse model of Alzheimer’s disease (AD). Recently, we evidenced a hypersynchronous brain network activity in young adult Tg2576 mice. As aberrant oscillatory activity can contribute to memory deficits, we wondered whether the long-lasting memory improvements observed after EE were associated with a reduction of neuronal network hypersynchrony. Thus, we exposed non-transgenic (NTg) and Tg2576 mice to standard or enriched housing conditions for 10 weeks, starting at 3 months of age. Two weeks after EE period, Tg2576 mice presented similar seizure susceptibility to a GABA receptor antagonist. Immediately after and 2 weeks after this enrichment period, standard and enriched-housed Tg2576 mice did not differ with regards to the frequency of interictal spikes on their electroencephalographic (EEG) recordings. Thus, the long-lasting effect of this EE protocol on memory capacities in Tg2576 mice is not mediated by a reduction of their cerebral aberrant neuronal activity at early ages.